Age at Marriage, Fertility and Infant-Child Mortality in a Lahore Suburb (PART II) (The Pakistan Development Review, 1976)
This study continues the discussion of demographic variables of in¬terest to the policy-maker in Pakistan. In this part an attempt is made to examine (i) the fertility experiences in relation to infant-child mortality for mothers in the survey area; and (ii) the differentials in the level of fertility and child mortality by income level, by educational levels of mothers and of fathers and by some relevant demographic variables.1 In pursuing the above two general objectives it is endeavoured to look for the variations in fertility, as indicated by children ever born to mothers. up to the time of the interview; and mortality, as indicated by the ratio of child deaths to the number of children ever born to a mother up to the time of inter¬view, in relation to each other and also in relation to such variables as age at marriage, family income, duration of marriage, mothers education and fathers education. Two approaches, which are also complimentary to each other, have been followed to study these relationships.